Occurrence of postharvest physiological disorders in 'Fuji' apples in response to orchard fertilization with nitrogen and potassium - Argenta L.C. (2013)
This study aimed to evaluate the interactive effects of orchard fertilization with nitrogen (N) and potassium (K) on physiological disorders of 'Fuji' apples after storage in regular air (RA) or controlled atmosphere (CA). 'Fuji' apple trees were grown on two Brazilian soils (Inceptisol and Entisol) annually fertilized with 0, 50, 100, and 200 kg ha-1 of both N and K2O from 1998 to 2006. In 2005 and 2006, fruits were harvested at optimum maturity for long-term storage, while in 2007 they were harvested two weeks before and two weeks after the optimum maturity. The combination of high N and K rates was associated with the high severity of bitter pit, superficial scald, CO2 injury and core browning. However, this effect depended on soil type, growing season, storage atmosphere and harvest date. The negative effect of high K2O rates on bitter pit, superficial scald and core browning was more evident in fruit grown on the Inceptisol than on the Entisol soil. In 2007, a greater negative effect of high K2O rates on bitter pit and superficial scald occurred in fruit harvested before the optimum maturity and stored in RA, while the effect of high K2O fertilization rates on CO2 injury occurred in fruit harvested after the optimum maturity and stored in CA. Effects of N fertilization rates on all physiological disorders were less consistent than those of high K2O rates. High severity of superficial scald in fruit grown on the Inceptisol was associated to low N rates when K2O rate was the lowest or, on the contrary, it was associated to high N rate when K2O rate was the highest. Since the effect of orchard fertilization varied according to the soil type, different strategies should be considered even for the same geographic region.